Policy for Distance Learning in Education in Higher Education Institutions: Experiences from Sudan - Saifaldin Idris Onia; Amel Farage Rmadan (Indonesian Journal of Educational Research and Technology, 2023)
The introduction of distance learning in education in universities has transferred the competition between them to a higher, global level also. However, Sudan is one of the African countries, suffering from many challenges that are related to technology such as poor network, lack of awareness, lack of commitment of institutions and instructors, and lack of network coverage to the remote areas. Therefore, this paper aimed to review the initiative of distance education in some Sudanese universities. In doing so, this paper followed a qualitative research approach to the type of case study research. The information for this study was derived from articles, books, online sources, reports, and documents. The paper reviewed distance education policy in some Sudanese Universities Such as the Open University of Sudan, University of Khartoum, Sudan University of Science and Technology, Al-Neelain University, and Al-Zaeem Al-Azhari University. It was normal that universities in Sudan needed to introduce their teachers and students to such distance education programs to achieve more excellence in teaching and learning. The paper suggests college officials should adopt policies to implement distance education in Sudanese universities.